Nursing Occupational Hazards of the Emergency Department in Teaching Hospitals affiliated to Tehran University of Medical Sciences - mohammad arab; mostafa hoseini; mohammad panahi; ziba khalili (Tehran University of Medical Sciences, 2015)
Background: Nurses are the largest group of health care providers and emergency department is known as a high risk ward in terms of occupational injuries. The aim of current study is to make out nursing occupational hazards in the emergency department among teaching hospitals affiliated to Tehran University of Medical Sciences. Materials and Methods: The study carried outed on 250 emergency department's nursing staff of hospitals affiliated to Tehran University of Medical Sciences. A valid and reliable questionnare used for data gathering by Simple random sampling method. Data analysed using descriptive snd inferential statistics. Results: The level of mean and SD of occupational injuries (2.87 ± 0.55) was assessed moderate. Among occupational hazzards, Psychosocial and institutional (3.58 ± 0.47) and Ergonomic (3.57 ± 0.71) ones were the most prevalent occupational hazards respectively and chemical hazards were the least important source of occupational injury. There was a statistical significant association of occupational injuries and variables such as hospital, years in practice, educational level, type of employment and training courses in occupational hazards (P<0.05). Conclusion: Nurses exposes a range of risk factors in different domains regarding occupational injuries. With the purpose of eliminating the risk factors, it needs to run various strategies in different domains. Applying ergonomic approaches, developing appropriate educational programs, providing adequate training in this area, etc., can result in reduceing occupational injuries and increasing their productivity.